Fe(III)-Catalyzed diastereoselective friedel-crafts alkylation-hemiketalization-lactonization cascade for the synthesis of polycyclic bridged 2-chromanol lactones - Borade, Balasaheb R.; Nomula, Rajesh; Gonnade, Rajesh G.; Kontham, Ravindar (Organic Letters, 2019)
An unprecedented Fe(III)-catalyzed Friedel-rafts alkylation-hemiketalization-lactonization cascade of electron-rich hydroxy arenes and distinctively functionalized unsaturated 4-keto esters is developed for the construction of polycyclic bridged 2-chromanol lactones. Following this simple and facile protocol, a broad range of products was prepared in good to excellent yields as a single diastereomer. An unusual conglomerate (enantiomerically pure polymorph) of 3ac is reported along with the absolute stereochemistry, and the remaining products were rigorously confirmed by single-crystal X-ray analysis and analogy.